"Dinamsoft 1.0": A Software for 3D biomechanical analysis of standard force training exercises and weightlifting - Gianikellis, K.; Skiadopoulos, A.; Barrios, J.; Fuentes, J. A. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The package "DinaSoft 1.0" is a software, developed in MATLAB environment, based in 3D Inverse Dynamics. It also includes special designed modules for Digital Signal Processing, EMG analysis and Stabilometry. It admits data obtained from different commercial electronic systems and instruments and after processing allows technical and scientific staff to obtain feasible information concerning biomechanics and motor control of the standard fitness, training and rehabilitation exercises.